Akademickie niestatki, czyli o niechlubnym żywocie polskich studentów w podróżach edukacyjnych po Europie Zachodniej od XVI do XVII wieku - Pietrzak, Jarosław (Biuletyn Historii Wychowania, 2014)
Initially, the article describes the perfect educational tour for a young nobleman in the 16th and 17th centuries. However, the ideal, as exemplified by the instructions and advice of parents, was in stark contrast with the actual behaviour of the students. Their excesses, triggered by leaving their family nests, their youth and pride in their heritage, took many forms. Among them were laziness, lack of respect for teachers, scuffles with other Poles or foreign students, drinking, gambling and fornicating. Such behaviour disgraced the young noblemen and led to them being expelled from universities, being incarcerated, or having to pay fines. Sometimes, the young men caught venereal diseases as a result of their sexual promiscuity, or sired illegitimate offspring. A number of them died due to excessive drinking and eating, or during street duels. The lives of Polish students have been described in numerous accounts from the universities of Padua, Bologna, Rome, Leiden and Altdorf.